PLANT REGENERATION THROUGH PROTOCORM-LIKE BODIES DERIVED FROM STEM THIN LAYER OF Anubias barteri var. Nana Petite - Giang K. T. Le; Tinh V. Nguyen; Ngan K. T Tran; Vy T. H. Dang; Phong V. Nguyen (Biotropia: The Southeast Asian Journal of Tropical Biology)
Article Highlights - Effective induction of PLBs from stem thin layer and shoot regeneration using specific BAP and auxin combinations. - Significant role of potato extract in enhancing shoot regeneration. - Highest shoot regeneration rate achieved with 3 mg/L BAP concentration.